The remnant life of aviation constructions components with small cracks - Игнатович, С. Р.; Йовенко, С. И.; Андрющенко, М. И.; Нинасивинча Сото, Ф. (Proceedings of National Aviation University (archive), 2000)
Experimental and theoretical studies relating to the behaviour of dispersed small cracks in a Ni-base alloy under LCF have been performed. A stochastic model to predict the crack length probability, density taking into account the random crack propagation was developed. The function of the remnant life distribution was obtained in terms of the stochastic model